2014
DOI: 10.1590/2176-9451.19.2.046-055.oar
|View full text |Cite
|
Sign up to set email alerts
|

The influence of orthodontic fixed appliances on the oral microbiota: A systematic review

Abstract: ObjectiveTo investigate whether there is scientific evidence to support the hypothesis that the presence of orthodontic fixed appliances influences the oral microbiota.MethodsThe search for articles was conducted in PubMed; ISI Web of Knowledge and Ovid databases, including articles published in English until May 17th, 2012. They should report human observational studies presenting the following keywords: "fixed orthodontic appliance" AND "microbiological colonization"; OR "periodontal pathogens"; OR "Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 24 publications
(49 reference statements)
3
99
0
4
Order By: Relevance
“…The present systematic review agreed with the conclusions arrived at by Freitas et al [5], which could be extended to any type of orthodontic appliance. The evidence of the selected sample was of medium-high level due to the lack of error of measurements analysis for the collection of material from oral sites.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present systematic review agreed with the conclusions arrived at by Freitas et al [5], which could be extended to any type of orthodontic appliance. The evidence of the selected sample was of medium-high level due to the lack of error of measurements analysis for the collection of material from oral sites.…”
Section: Discussionsupporting
confidence: 92%
“…Discussions were held to resolve any disagreements; when a resolution could not be found, a third review was consulted. Data extraction from the selected papers was performed independently by two review authors who adopted a template similar to that of Freitas et al [5]. The template was adapted to the necessities of our study and is shown in Table 2 [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brackets and orthodontic accessories facilitate plaque accumulation and compromise oral hygiene maintenance which lead to an increase in oral bacteria count during orthodontic treatment [25]. Despite myriad progresses in orthodontics, fixed orthodontic treatment is still accompanied with a high risk of formation of white spot lesions which are found in more than 50% of orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the most remarkable change occurs 6 months after the beginning of orthodontic treatment and has a significant increase in the prevalence of two cariogenic micro‐organisms, namely S. mutans and Lactobacillus spp. On the one hand, the increase in the rate of S. mutans following the use of orthodontic appliances can be explained by the irregular nature of their surfaces, which promotes the growth of these bacteria . Regardless of moderate levels of evidence, the presence of fixed appliances influences the quantity and quality of the oral flora …”
Section: Discussionmentioning
confidence: 99%